2020
DOI: 10.1002/pbc.28738
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic disparities in survival of children with brain and central nervous tumors in the United States

Abstract: Background: Despite improvements in overall survival for pediatric cancers, treatment disparities remain for racial/ethnic minorities compared to non-Hispanic Whites; however, the impact of race on treatment outcomes for pediatric brain and central nervous system (CNS) tumors in the United States is not well known. Methods: We included 8713 children aged 0-19 years with newly diagnosed primary brain and CNS tumors between 2000 and 2015 from the Census Tract-level SES and Rurality Database developed by Surveill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
(143 reference statements)
0
9
0
Order By: Relevance
“…Updated epidemiological data on the burden of brain and CNS cancers is thus required. However, there are few reports on the epidemiology of brain and CNS cancers in all age groups [14][15][16]. Some studies have focused only on the incidence and mortality of brain and CNS tumors in children, while ignoring incidence and mortality in elderly patients.…”
Section: Open Accessmentioning
confidence: 99%
“…Updated epidemiological data on the burden of brain and CNS cancers is thus required. However, there are few reports on the epidemiology of brain and CNS cancers in all age groups [14][15][16]. Some studies have focused only on the incidence and mortality of brain and CNS tumors in children, while ignoring incidence and mortality in elderly patients.…”
Section: Open Accessmentioning
confidence: 99%
“…1 Minority children are less frequently diagnosed with these tumors as White children have an incidence rate of 5 cases per 100,000 and Black and Hispanic children have a rate of 4 cases per 100,000 2 ; however, Black and Hispanic children experience an increased risk of death in comparison with White children 3,4 even after accounting for age, socioeconomic status, stage of disease, and treatment as adjustment factors in the analysis. 5 Often times, racial/ethnic survival disparities are explained by or linked to existing differences in socioeconomic status. 6 However, in a mediation analysis examining the role of socioeconomic status between race/ethnicity and survival from childhood cancers, 7 most of the observed associations were only minimally explained by, or were largely independent of, socioeconomic status, and strong direct effects of race/ethnicity were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Brain tumors are the most common solid tumors in children 1 . Minority children are less frequently diagnosed with these tumors as White children have an incidence rate of 5 cases per 100,000 and Black and Hispanic children have a rate of 4 cases per 100,000 2 ; however, Black and Hispanic children experience an increased risk of death in comparison with White children 3,4 even after accounting for age, socioeconomic status, stage of disease, and treatment as adjustment factors in the analysis 5 . Often times, racial/ethnic survival disparities are explained by or linked to existing differences in socioeconomic status 6 .…”
Section: Introductionmentioning
confidence: 99%
“…1,8,9 The COG AHEP0731 study We identify that in the survival of patients with HB, racial and ethnic disparities exist, which have not been previously described, but have been observed with other cancers, including hepatocellular carcinomas, brain and central nervous system tumors, leukemias, and lymphomas. [29][30][31][32] Specifically, we found that NH Black race or ethnicity was a significant risk marker of reduced overall survival in multivariable Cox regression analysis. Race or ethnicity overall was not found the model.…”
Section: Discussionmentioning
confidence: 72%